2020
DOI: 10.3390/jcm9092989
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anticholinergic Medication Burden on Mobility and Falls in the Lifestyle Interventions for Elders (LIFE) Study

Abstract: Anticholinergic cognitive burden (ACB) may be associated with detrimental effects on mobility and physical independence in older adults. We evaluated the incidence of major mobility disability (MMD), persistent major mobility disability (PMMD), and injurious falls among participants within the Lifestyle Interventions for Elders (LIFE) trial according to varied anticholinergic burden levels. Participants aged 70–89 years were randomized to a physical activity (PA) or successful aging (SA) intervention and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Eight studies [14][15][16][17][18][19][20][21] met our criteria and were analysed to identify fall risk associated with ACB and to identify if the level of risk differs between ACB measures.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [14][15][16][17][18][19][20][21] met our criteria and were analysed to identify fall risk associated with ACB and to identify if the level of risk differs between ACB measures.…”
Section: Resultsmentioning
confidence: 99%
“…Zia et al 30 found that an ACB score ≥ 1 was associated with recurrent and injurious falls in older community-dwelling persons, but this association did not remain statistically significant after adjustment for gait and balance impairment. Squires et al 31 also examined the association between ACB scores and injurious falls in older community-dwelling persons and found that persons with a high ACB score had an increased risk for injurious falls over an average follow-up of 2.6 years. In contrast to our study, they only investigated falls resulting in a fracture or injury requiring hospitalization, while we also examined falls that did not result in injury.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, data on falls was collected by following patients for several months to years. 20 , 22 , 31 Following patients for a longer period of time increases the risk and amount of falling. Moreover, many patients in our study were exposed to anticholinergic drugs, but the median ADB score per patient was relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Squire et al (Squires et al 2020) reported the presence of a strong association between those using medications with anticholinergic properties and mobility disability outcomes and injurious falls when compared to those not using these medications. Using the drug burden index, a study involving 602 residents of residential aged care facilities found a significant increased incidence in falls with over a 12-month period for those with low and high anticholinergic and sedative drug exposure (N.M. et al 2011).…”
Section: Discussionmentioning
confidence: 99%